Reliability evaluation of power transformers using partial discharge testing and measurement of low molecular mass acids in insulating oil - Filho, Armando B.; Carriel, Lazaro P.; Aguiar, Jose H.; Galdeano, Claudio A.; Malaquias, Paulo E.; Pinto, Andre J.G.; Pissolato, Jose; Kurokawa, Sergio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
The transformer is a fundamental part in electrical power systems. This equipment represents high cost and requires greater attention during maintenance activities. To avoid interruptions, it is important to evaluate the lifetime of transformers efficiently, such that repair and replacement can be performed in a planned and preventive way. The present study aims to develop a methodology for the evaluation of the reliability of power transformers using partial discharge testing of the insulating oil of transformers in operation, both in the field and in laboratory studies.
Keywords: Aging; condition-based maintenance; insulation; lifecycle; reliability